2007
DOI: 10.1002/er.1284
|View full text |Cite
|
Sign up to set email alerts
|

Size effects on the hydrogen storage properties of nanostructured metal hydrides: A review

Abstract: Hydrogen is considered a good energy carrier candidate for future automotive applications that could be part of a carbon-free cycle. Metal hydrides are often preferred over pressurized gas and other hydrogen storage methods because of their gravimetric and volumetric storage capacities and safe operating pressures. In addition to the hydrogen storage capacity, other properties that have often been disregarded must now be addressed before hydrogen storage in metal hydrides becomes feasible. The slow hydriding/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(195 citation statements)
references
References 84 publications
3
161
0
2
Order By: Relevance
“…In this process, the rate-limiting step changes from the dissociation and penetration of hydrogen at the metal/H 2 interface to the nucleation of the hydride phase, and possibly the diffusion of hydrogen through the metal hydride layer that forms around the metal particle. 54 We expect to see similar processes in Li 2 NH.…”
Section: Hydrogenation Of Li2nhmentioning
confidence: 83%
“…In this process, the rate-limiting step changes from the dissociation and penetration of hydrogen at the metal/H 2 interface to the nucleation of the hydride phase, and possibly the diffusion of hydrogen through the metal hydride layer that forms around the metal particle. 54 We expect to see similar processes in Li 2 NH.…”
Section: Hydrogenation Of Li2nhmentioning
confidence: 83%
“…Fortunately, systematic studies (11-13) of the evolution of desorption energies and electronic structure of Mg n H 2n clusters as a function of n have shown that the properties have converged when n is Ϸ30. Therefore, a 31 formula unit MgH 2 nanocluster was used in the present work to study the effect of doping in nanostructures; and given the recent advances in synthesis of nanoscale particles (14) and the move in the hydrogen storage community toward highly nanostructured hydrogen storage materials (15), clusters of the size considered here may soon become more than model systems.…”
Section: Mgh 2 Cluster Modelmentioning
confidence: 99%
“…However, the temperature for releasing hydrogen still remains far above the requirements for ambient condition applications. Moreover, a major drawback of this approach is that it is accompanied by a significant reduction of the storage capacity [5]. Recent studies have shown that hydrogen adsorbed on nanostructured Mg can be released at a low temperature and it can be even significantly lowered if other compounds such as carbon nanotubes are added to the material [6].…”
Section: Introductionmentioning
confidence: 99%